VALENCY OF CHILD SPEECH IN THE YOUTUBE CHANNEL “STEVE TV SHOW”: SYNTACTIC AND SEMANTIC ANALYSIS - Izzah, Linatul Laili; Indah, Rohmani Nur (Universitas Islam Sumatera Utara (UISU), 2023)
Current linguistic studies tend to investigate sentence structure to determine the form of valency in written sentences. However, the study of valency in verbal communication still needs more exploration. This study investigated the types of valency and its arguments used by Ariana Jalia, a 6-year-old child, in her spontaneous utterances during the interview on ‘Steve TV Show’. As a qualitative descriptive study, the purpose was to gain a deep understanding of valency and its arguments found in the child's speech. In the field of semantics, the findings of this study indicated that the utterances produced by Ariana contained four types of valency zero, twelve types of valency one, and three types of verb valency. In addition, the semantic analysis investigated the thematic roles assigned to the argument verbs used by the child. Viewed from the agents, themes, causes, and topics of what Ariana described in her narrative, she employed transitive verbs. The findings shed light on the way children used language in informal and conversational settings and how they constructed sentences with different verb structures to convey their thoughts and ideas. It also highlights the importance of understanding the grammatical structures used by children in order to better support their language development. The need for further research suggests that there is still much to be learned about the early stages of language development and how children use language in various settings.